2007
DOI: 10.1007/s11627-007-9093-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an interaction effect during in vitro rooting of oil palm (Elaeis guineensis Jacq.) somatic embryo-derived plantlets

Abstract: In vitro rooting of oil palm shoots derived from somatic embryos was achieved through a single-phase protocol in which three shoots are cultured in the same culture tube on an α-naphtaleacetic acid-enriched culture medium. Rooting performance was dependent on both the genetic origin and initial size of the shoot explants. All shoots from a given tube showed a tendency to give roots of the same type, independent of the original size of the explant. Whatever the clonal line, longer-size shoots (Ltype: >9 cm) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
9
1
4
Order By: Relevance
“…Planlet yang telah memiliki sistem perakaran yang baik akan lebih cepat tumbuh dan berkembang saat diaklimatisasi (Hazarika, 2003). Konan et al (2007) menggunakan tiga planlet kelapa sawit per tabung kultur pada medium padat dengan NAA 1 mg/L yang menghasilkan persentase pembentukan akar terbaik sebesar 66%. Untuk produksi komersial, persentase pembentukan akar planlet kelapa sawit ini masih perlu ditingkatkan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Planlet yang telah memiliki sistem perakaran yang baik akan lebih cepat tumbuh dan berkembang saat diaklimatisasi (Hazarika, 2003). Konan et al (2007) menggunakan tiga planlet kelapa sawit per tabung kultur pada medium padat dengan NAA 1 mg/L yang menghasilkan persentase pembentukan akar terbaik sebesar 66%. Untuk produksi komersial, persentase pembentukan akar planlet kelapa sawit ini masih perlu ditingkatkan.…”
Section: Pendahuluanunclassified
“…Akar primer berwarna putihkekuningan atau putih-kecoklatan dengan akar sekunder berwarna putih sebagaimana ditunjukkan pada Gambar 3B. Konan et al (2007) berhasil menginduksi akar planlet kelapa sawit secara in vitro dalam medium MS padat modifikasi yang ditambah dengan NAA 1 mg/L. Keragaan atau kelas akar terbaik diperoleh pada umur 12 minggu.…”
Section: Kelas Akarunclassified
See 1 more Smart Citation
“…Some of the plantlets are not able to form roots although they have future radicles. If the plantlets have already good aerial parts (shoots), root induction can be done in vitro in the laboratory with rooting frequency of 66-92% (Rival et al 1997;Konan et al 2007;Ibrahim et al 2009;Nizam and Te-chato 2009;Riyadi and Sumaryono 2010) or ex vitro during acclimatization period in the greenhouse or nursery.…”
Section: Introductionmentioning
confidence: 99%
“…However, results reported by Sumaryono et al (2012) revealed that increasing the concentration of sucrose or other carbohydrates did not favor the growth and vigor of sago plantlets. Rooting of the plantlets was conducted in liquid medium as commonly performed in oil palm plantlets (Konan et al 2007). Good vigor and root system of plantlets increased the survival rate of plantlets during acclimatization.…”
mentioning
confidence: 99%